Novel 2-Hydroselenonicotinonitriles and Selenopheno[2, 3-b]pyridines: Efficient Synthesis, Molecular Docking-DFT Modeling, and Antimicrobial Assessment - Abdellattif, Magda H.; Abdel-Rahman, Adel A. H.; Arief, Mohamed Mohamed Helmy; Mouneir, Samar M.; Ali, Amena; Hussien, Mostafa A.; Okasha, Rawda M.; Afifi, Tarek H.; Hagar, Mohamed (Frontiers in Chemistry, 2021)
Selenium containing heterocyclic compounds gained great interest as bioactive molecules as of late. This report explores the design, synthesis, characterization, and antimicrobial screening of new pyridine derivatives endowed with selenium moieties. A one-pot multicomponent system with a solvent-free, microwave irradiation environment was employed to afford this series. The spectroscopic techniques were exploited to verify the structures of the synthesized derivatives. Additionally, the agar diffusion method was employed to determine the antimicrobial activity of all the desired compounds. Of all the synthesized molecules, 9b, 12b, 14f, and 16d exhibited well to remarkable antibacterial and antifungal activities. Moreover, derivative 14f demonstrated the most potent antibacterial and antifungal performance. The results were also supported by molecular docking studies, utilizing the MOE (molecular operating environment) which revealed the best binding mode with the highest energy interaction within the binding pocket. Lastly, theoretical DFT calculations were carried out in a gas phase at B3LYP 6-311G (d,p) basis set to predict the molecular geometries and chemical reactivity descriptors. DFT results have been used to illustrate that molecular docking findings and biological activity assessments.